FACTORS AFFECTING NURSING STUDENTS’ HESITANCY TO SPEAK ENGLISH: A STUDY AT UNIVERSITAS PELITA HARAPAN - Pramusita, Santa Maya; Situmorang, Komilie; Saputra, Bima Adi (English Review: Journal of English Education, 2024)
Proficiency in spoken English is commonly seen as avital aspect of language learning. Regrettably, a significant portion of ESP learners exhibit reluctance to engage in oral communication inside the language learning classroom, which can be attributed to various reasons. Therefore, the present study aims to investigate the relationship among linguistic factor, psychological factor, and sociocultural factor on nursing students’ hesitancy to engage in oral communication exercises. The data were collected using a questionnaire, while the association between variables was tested using the Gamma statistical test. The participants of this study consisted of second-year nursing students in a private university in Tangerang. The sample was determined using the convenience sampling technique, which yielded a total of 195 respondents. A noteworthy correlation had been observed between the linguistic factors (p-value 0.001), psychological factor (p-value 0.001), and sociocultural factor (p-value 0,004) in connection to nursing students’ hesitancy. The correlation between factors is moderately strong, with the variables of all factors indicating a positive association with reluctance. Consequently, the higher the factors, the greater the nursing students’ willingness to speak English, and vice versa. The lecturers should hence foster a safe and accepting environment in the classroom through fostering connections between themselves and the students.